Contributions of quantitative methods to the study of gender and crime, or bootstrapping our way into the theoretical thicket - Kruttschnitt, Candace (Journal of quantitative criminology, 1996)
Researchers concur on the importance of gender to the study of crime but not on the particular methodological strategy that should be used when studying the gender-crime relationship. This paper examines the actual and potential contributions of quantitative methods for unpacking the gender-crime relationship. Three bodies of literature pertaining to the gender-crime relationship are examined: (i) offending, (ii) victimization, and (iii) criminal justice processing. The findings from this review indicate that while much knowledge about the gender-crime relationship has been uncovered with quantitative data, a commensurate amount of theoretical knowledge does not exist. The author concludes with substantive and methodological suggestions for furthering our understanding of the gendercrime relationship.